Impact of Omicron infection on childhood health: the Beijing long-COVID study - Bo Zhou; Qi Xu; Shaoli Li; Jianhong Wang; Junting Liu; Junting Liu; Ting Zhang; Xia Qu; Xi Wang; Lili Zhang; Xiaoli Liu; Jialu Gu; et al. (Frontiers in Public Health)
PurposeThe aim of this prospective study was to assess the dynamic changes of persisting symptoms among children aged 6–18 years during 1–2 months after the Omicron infection based on the modified SBQ-LC in the Tongzhou cohort, Beijing.MethodsThis study includes 4 serial surveys performed within January 7–9, January 14–16, January 21–23, and February 12–14 in 2023, respectively. The prediction of age and survey for eight domains in the Rasch 0–100 linear score was undertaken by generalized additive mixed model.ResultsTotal 1,536 children (median age: 13 years, boys: 49.9%) had completed questionnaires across 4 surveys. Information on 51 symptoms was collected, with each scored on a 4-point rating scale. Generally, the distribution of age with all domains followed the N-shaped geometry, and that of survey followed the inverse J-shaped geometry. The Rasch linear score hit the lowest level among children aged 6–8 years, and reached the peak among children aged 12–13 years. The scores of all domains sharply declined from the first to the third survey, and remained stable between the third and the fourth survey. At the fourth survey, 95.05 and 51.37% children still had one or more problems relating to breathing and mental health, respectively, and the percentage of rest six domains was reduced to less than 20%.ConclusionOur findings indicate the multifaceted impact of Omicron infection on childhood health, especially among children aged 12–13 years. Moreover, breathing and mental health related problems still persisted during 1-to-2-month Omicron infection period.